2006
DOI: 10.1007/s00125-006-0518-7
|View full text |Cite
|
Sign up to set email alerts
|

Age, overweight and physical inactivity increase the risk of latent autoimmune diabetes in adults: results from the Nord-Trøndelag health study

Abstract: Aims/hypothesis Latent autoimmune diabetes (LADA) is a common form of diabetes, yet the risk factors are poorly characterised. The aim of this study was to investigate the influence of age, overweight and physical activity on the risk of LADA. Methods We analysed age, overweight and physical inactivity and the incidence of LADA in 38,800 men and women, observed between 1984 and 1986 and 1995 and 1997 as part of the Nord-Trøndelag Health Survey. We also compared such factors with incident cases of type 2 (n=738… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 11 publications
(11 reference statements)
7
51
1
1
Order By: Relevance
“…Therefore, there is no evidence to suggest that autoimmune diabetes is due to decreased insulin sensitivity; instead, decreased insulin sensitivity might predispose to an earlier time of diagnosis. Such decreased insulin sensitivity could explain why age, overweight, and physical inactivity are as strongly predictive of LADA as they are of type 2 diabetes (15,16). These present observations indicate that metabolic syndrome is as common in adults with autoimmune diabetes as it is in normal subjects.…”
Section: Statistical Analysesmentioning
confidence: 53%
“…Therefore, there is no evidence to suggest that autoimmune diabetes is due to decreased insulin sensitivity; instead, decreased insulin sensitivity might predispose to an earlier time of diagnosis. Such decreased insulin sensitivity could explain why age, overweight, and physical inactivity are as strongly predictive of LADA as they are of type 2 diabetes (15,16). These present observations indicate that metabolic syndrome is as common in adults with autoimmune diabetes as it is in normal subjects.…”
Section: Statistical Analysesmentioning
confidence: 53%
“…Follow-up time varied from 3 [42] to 23.1 [60] years. Twelve studies were conducted in the USA [12,14,35,38,46,58,[60][61][62][63][64][65], six in Asia [47,57,59,[66][67][68], two in Australia [40,42] and eight across Europe [13,36,37,39,41,[69][70][71]. All cohorts relied on self-reported PA collected using questionnaires or by interview, apart from one study in Hawaiians [58].…”
Section: Resultsmentioning
confidence: 99%
“…In the context of type 2 diabetes, earlier studies have found that dose-response curves may be different for Asian Ding et al (2015) [42] Burchfiel et al (1995) [58] Magliano et al (2008) [40] Steinbrecher et al (I) (2012) [38] Grøntved et al (2012) [61] Demakakos et al (2010) [71] Haapanen et al (II) (1997) [36] Krishnan et al (2009) [64] Chien et al (2009) [68] Folsom et al (2000) [62] Carlsson et al (2007) [41] Ekelund et al (II) (2012) [39] Nakanishi et al ( 2004) [57] Steinbrecher et al (II) (2012) [38] Meisinger et al (II) (2005) [37] Okada et al (2000) [66] Grøntved et al (II) (2014) [35] Fretts et al (2009) [46] Lynch et al (1996) [13] Meisinger et al (I) (2005) [37] Haapanen et al (I) (1997) [36] Subtotal (I Indians who may require more PA to be protected from their relatively higher susceptibility to develop type 2 diabetes [72,73]. A potential strength of our present analyses is the expression of PA exposure dose in MMET h/week rather than just MET h/week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the role of overweight in the development of LADA may depend on the severity of the underlying autoimmune process. Only one prospective study based on 11 years follow-up of the Norwegian Nord-Trøndelag Health Study (HUNT Study) estimated the risk of LADA in relation to overweight/obesity [20]. This study was based on only 81 individuals; hence, the influence of excessive weight on more or less autoimmune forms of LADA could not be explored, and confounding control was limited.…”
Section: Introductionmentioning
confidence: 99%